Review Buku: Meneguhkan Dakwah Bi al-Kitabah Melalui Fikih Jurnalistik - Yusron, Alfi (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2014)
.